Tripartite evolutionary game analysis of governance mechanism in Chinese WEEE recycling industry. (May 2022) - Li, Bangyi; Wang, Qixiang; Chen, Baixue; Sun, Ting; Wang, Zhe; Cheng, Yongbo
Highlights: Combine product eco-design and qualified disassembly in governance mechanism. Consider the reward-penalty mechanism in the Chinese WEEE recycling industry. Enrich the theoretical research on formal and informal collectors. Abstract: The rapidly increase in waste electrical and electronic equipment (WEEE) poses challenges to the government to manage the WEEE recycling industry. In order to better understand and improve the governance mechanism in the WEEE recycling industry, taking China as an example, we construct a tripartite evolutionary game model consisting of the manufacturer, the collector, and the government by underscoring product eco-design and qualified disassembly. First, we obtain the evolutionary stability strategy (ESS) by calculating the replicator dynamic equation and the stability analysis of equilibrium points. Then, we examine the feasibility and rationality of the evolutionary game model by analyzing ESSs corresponding to different stages of the WEEE recycling industry. Finally, we explore the ramifications of the governance mechanism on the behaviors of the manufacturer's product eco-design and the collector's qualified disassembly through a numerical example. We find that the evolutionary game model exists eleven equilibrium points and six possible ESSs, and the choice of each ESS depends mainly on the trade-off between costs and revenues for each stakeholder. Through the numerical study, we observe that the current Chinese WEEE governance mechanism is not effective. We also observe that the manufacturer's willingness to implement product eco-design is decreasing in the tax rate but increasing in the environmental tex, and the collector's willingness to recycle WEEE through a compliance process is increasing in both the subsidy and the penalty. We suggest that the government focuses on improving the reward-penalty mechanism, establishing appropriate WEEE disposal fund levy and subsidy standards, and removing informal collectors to promote the healthy development of WEEE recycling industry.